Can customised sfh charts predict SGA in unexplained stillbirth?. (18th April 2012) - Ingram, E; Sharp, A; Roberts, D
Abstract : Small for gestational age (SGA) fetuses are at greater risk of stillbirth. Standard antenatal care utilises symphyseal fundal height (SFH) for the identification of SGA. We explored how useful SFH measurements were in identifying fetuses <10 th centile on customised birthweight charts in our stillbirth population. Retrospective review of unexplained stillbirths at Liverpool Women's Hospital (LWH) from 2005 – 2009. Women with multiple growth scans or no SFH measurements recorded were excluded from analysis. SFH measurements were plotted on LWH population specific and customised (Gestation.net) SFH charts. SFH centiles were compared with the customised birthweight centile to assess accuracy. Data was available for 46/61 eligible stillbirths. 28 (61%) of these cases had birthweight <10 th centile. Population specific SFH charts identified none of the cases of SGA. 86% of these SFH measurements were plotted between 50 th - 90 th centile, 7% above the 90 th centile and the remaining between 10-50 th centile. Customised charts correctly identified SGA in 7 cases (25%). 43% were plotted between 50 th - 90 th centile and 32% were above the 90 th centile. Although customised SFH charts appear to identify more SGA fetuses than population specific charts, the sensitivity is only 25%. Benchmarking with other regions may help identify errors in correct measurement of SFH or other confounders. The failure to identify a higher proportion of SGA fetuses despite customised SFH measurements highlights the limitations of this technique in modern obstetric practice. We suggest it is time to explore ultrasound packages for identifying the small baby to reduce stillbirth.